Analisis Keterampilan Mahasiswa Fakultas Tarbiyah Dan Ilmu Keguruan IAIN Bukittinggi Dalam Menjelaskan Materi Pelajaran - Irna Andriati; Zulfani Sesmiarni (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
AbstractThis study aims to analyze the skills of explaining lessons to prospective teacher students at the FTIK IAIN Bukittinggi. The research method used is qualitative with a content analysis approach. The results of the study showed that students in mastering the skills explained away from other skills. Skills are explained as a basis for seating the concepts that will be conveyed to students. The teacher is like the man behind the gun. Any caliber of weapons to be used, if the teacher is not proficient in operationalizing the explaining skills, the results will be far from what is expected. Conversely, even though the weapon that the teacher will use is only a stone, but with his expertise, he will be able to reach the target optimally. As FTIK students and prospective teachers must be able to master the skills to explain well. One way that can be done is by mastering the material to be taught and doing a lot of practice. The more practice the more experience is generated. The teacher is never born just like that, but the teacher exists because of the practice. Keywords: Explaining Skills, Subject Matter.